E-Mechatronics: Digital Content in Transformation of Teaching and Learning - Pavlasek, Pavel (Communications - Scientific letters of the University of Zilina, 2007)
This article deals with mechatronics as a one of the leading and fast growing world industrial and economic sectors, for which in educational niche it is critical to provide enriched digital contents through a homogenous training tool. Mechatronics is from now based on historical know-how but truly needs to evolve through enhanced collaboration with various industries: home and office products, transport, automotive, space, etc. Providing the eContent of mechatronics as a common training tool that will help these multidisciplinary collaborations and strength exchanges within these scientific and technological areas eMECHATRONICS will position itself at the junction of mechanics, electronics and software engineering. The article is based on more than 15 years experiences at University of Žilina in mechatronics, and linguistic contribution, as well as in the analysis in the existing digital content, knowledge and know-how available at the educational, professional and public level in these different scientific and technological domains. Such eContent will serve, as described in this article, to propose and enhance web-based training services, providing mechatronics-related knowledge according to the individual level, language competency and needs of its users, may they be students, professionals or individuals.